BIBLIOMETRIC STUDY ON THE APPLICATION OF MATHEMATICS IN STEM EDUCATION - A’alaf, Rasyida; Abu, Zunainah; Abdollah, Badariah (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
The integration of mathematics within STEM education has received increasing scholarly attention, reflecting its essential role in preparing students for interdisciplinary problem-solving and global competitiveness. However, despite its growing significance, limited comprehensive studies have mapped research patterns, influential contributions, and collaboration networks in this domain. This study aims to fill that gap through a bibliometric analysis of publications on the application of mathematics in STEM education. Data were collected from the Scopus database using advanced searching techniques with the keywords “mathematics,” “education,” and “STEM,” covering the period between 2015 and 2025. After applying inclusion and exclusion criteria, a total of 776 articles were retrieved. The dataset was subsequently processed and harmonized using OpenRefine to ensure consistency. Statistical analyses, publication trends, and citation distributions were examined using the Scopus analyzer, while VOSviewer software was employed to visualize keyword co-occurrences, authorship patterns, and international collaboration networks. The findings reveal a steady increase in research output, peaking in 2024–2025, with the United States, Indonesia, and Germany emerging as the most productive countries. Highly cited articles highlight themes such as word problem-solving, interdisciplinary STEM integration, and digital innovations in mathematics education. Keyword analysis identified dominant themes around “mathematics education,” “STEM education,” “teacher education,” and emerging topics such as “computational thinking,” “artificial intelligence,” and “sustainability,” reflecting the field’s evolving priorities. Co-authorship network analysis further showed strong international collaboration clustered among developed and emerging economies. Overall, this study contributes to a deeper understanding of the intellectual structure, thematic evolution, and global collaboration trends in mathematics-focused STEM education research, providing valuable insights for educators, policymakers, and future researchers.